Connecting Colombia's Poor to Natural Gas Services : Lessons Learned from a Completed Output-Based Aid Project - Mandri-Perrott, Cledan (World Bank, Washington, DC, 2012)
The Global Partnership on Output-Based Aid (GPOBA) has recently completed a project that made 35,000 new natural gas connections to poor households in Colombia's Caribbean coastal region. This partnership between GPOBA and Fundacion Promigas (a charitable foundation established by Colombian gas distribution holding company, Promigas) has resulted in substantial benefits to Colombia's poor population. Because in-home natural gas connections provide a safer, more environmentally friendly, and less expensive substitute to previously used fuels, poor families are enjoying the long-term advantages from this program's one-time subsidies. This note explores the results of this program and draws lessons for future projects.